2021
DOI: 10.1038/s41598-021-95532-3
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell residency in the nasal mucosa may partially explain respiratory disease severity across the age range

Abstract: Previous studies focusing on the age disparity in COVID-19 severity have suggested that younger individuals mount a more robust innate immune response in the nasal mucosa after infection with SARS-CoV-2. However, it is unclear if this reflects increased immune activation or increased immune residence in the nasal mucosa. We hypothesized that immune residency in the nasal mucosa of healthy individuals may differ across the age range. We applied single-cell RNA-sequencing and measured the cellular composition an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 34 publications
0
29
0
1
Order By: Relevance
“…Furthermore, the milder condition in the younger patient cohort may be closely related to the potent innate immunity of the children. Previous studies (Vono et al, 2021;Winkley et al, 2021;Pierce et al, 2021), indicated that, compared with adults, younger children had a more robust mucosal response to prevent immune escape of the virus and generate an immediate barrier to viral infection. What is more, a recent study documented that the activated interferons in the respiratory mucosa of the children may protect them against SARS-CoV-2 infection (Yoshida et al, 2021), in which children had a significant increase of naive lymphocytes and decrease of NK cells in the systemic response, quite different from adults who had more cytotoxic T-cells (CTL) that were interferon-responsive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the milder condition in the younger patient cohort may be closely related to the potent innate immunity of the children. Previous studies (Vono et al, 2021;Winkley et al, 2021;Pierce et al, 2021), indicated that, compared with adults, younger children had a more robust mucosal response to prevent immune escape of the virus and generate an immediate barrier to viral infection. What is more, a recent study documented that the activated interferons in the respiratory mucosa of the children may protect them against SARS-CoV-2 infection (Yoshida et al, 2021), in which children had a significant increase of naive lymphocytes and decrease of NK cells in the systemic response, quite different from adults who had more cytotoxic T-cells (CTL) that were interferon-responsive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Though we investigated IAV receptors only in epithelial cells, we recognize that immune cells such as pDCs express them as well. However, we believe that the epithelial cells are the major source in the reproductive age group because the frequencies of epithelial cells outstrip the frequencies of immune cell populations in the nasal epithelium by a factor of approximately 10:1 [ 35 ]. Increased availability of these receptors could potentially promote enhanced entry of IAV into respiratory epithelial cells raising the possibility that pregnant women could be more susceptible to IAV infection, in addition to suffering from severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…Single cell sequencing analysis of upper airway cells reveal there are approximately twice as many cells that are ACE2 + /TMPRSS2than are ACE2 + /TMPRSS2 + (Supplementary Table S1) [32][33][34][35][36][37] . We considered whether the early replication advantage of Omicron in the hNEC was conferred by an expansion of the number of target cells available for initiation of infection, as the endosomal pathway enables ACE2 + /TMPRSS2cells to be infected.…”
Section: Omicron Enters Cells More Efficiently Through the Endosomal ...mentioning
confidence: 99%